The use of silence as a monitor in EAL Australia - Ekici, Gail (Association for Scientific Computing Electrical and Engineering(ASCEE), 2025)
This mixed methods study has highlighted that students in lower level of EAL in Ausytalia have used silence to monitor their speeches. The study surveyed 148 student and teachers and results highlighted that teachers did not know about the adult silent period. Findings show that that their silent period was not treated by their teachers due to ‘pedagogical barriers’. Competent Bilinguals said that there was too much emphasis on form rather than meaning. The main reason for paucity on the this topic is because for several decades the teaching of English as an additional language (EAL) has focused on communicative language teaching (CLT) to encourage students to use English to make meaningful conversations. Proficency silence as an adult learnier in EAL is crusal and needs to understood by educators.